Pengaruh Kualitas Sumber Daya Manusia, Kepuasan Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Kementerian Agama Kabupaten Lebong Provinsi Bengkulu - Firda Firdaus; Sunda Ariana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to find out the condition of employee performance, to find out the condition of human resource quality, to find out job satisfaction, to find out the condition of the work environment, to find out the influence of human resource quality, job satisfaction and work environment on the performance of employees of the Ministry of Religion of Lebong Regency, Bengkulu Province. In this study, data was obtained by distributing questionnaires to 187 employees as sample respondents. To analyze the influence of Human Resource Quality (X1), Job Satisfaction (X2), Work Environment (X3) on Employee Performance (Y) at the Ministry of Religion office of Lebong Regency, Bengkulu Province, data analysis techniques were used using Structural Equation Modelling (SEM) based on Partial Least Square (PLS)3.0 The results of this study show that: 1. There is a significant and positive influence of the quality of human resources on job satisfaction; 2. There is a significant and positive influence of the work environment with job satisfaction; 3. There is a significant and positive influence of job satisfaction with employee performance; 4. There is a significant and positive influence of the quality of human resources on performance; 5. There is a significant influence of the work environment on performance; 6. There is a significant influence of Job Satisfaction with Performance.